PRAKTIK KOALISI PARPOL PILPRES DAN WAPRES DALAM SISTEM PRESIDENSIAL INDONESIA - Rika Novitasari (Jurnal Magister Hukum Perspektif, 2019)
In the Indonesian context, a coalition is formed before the Presidential and Vice Presidential Elections with the aim of winning the candidates carried by the coalition. A coalition that has been formed does not guarantee that the combined parties in the coalition will always support government programs. The problems faced are: (1) What is the practice of political coalitions in the Indonesian Presidential system, and (2) how are the legal implications of political coalitions formed in the 2014 presidential election. In this study, the authors used research that is normative juridical by focusing the research on literature data or secondary data. Based on the results of the theoretical study, the following conclusions can be drawn: The coalition's practice in the presidential system in Indonesia is associated with the electoral system occurs due to the unfulfillment of the voting conditions to propose the pair of presidential candidates and vice presidents. Keywords: Coalition, political parties, election, presidential system